the the Use of Shopping Card Members in the Retail Industry in the Perspective of Marketing Mix and Shariah Maqashid - rifai, mochamad novi; Hakim, Arif Luqman (Falah: Jurnal Ekonomi Syariah, 2022)
To discuss further the connection of Member Card with product promotion. That Member Card is one part of the promotion mix that companies can use to build relationships with consumers and communicate the values of these products persuasively. This aims to understand the promotion mix view of the member card and understand the concept of the member card that seen from Maqashid Sharia perspective. This qualitative research uses a descriptive approach. The research concludes that the promotion mix that is often used by card issuers for member cards for members is in the form of direct selling. While the concept used by consumers in choosing or deciding to become a member card member is in accordance with Maqashid Sharia, namely in an attitude of prudence in spending assets on items that are not needed and being able to save by using the member card feature